1957
DOI: 10.1063/1.1743661
|View full text |Cite
|
Sign up to set email alerts
|

Ionization and Dissociation of Perchlorylfluoride by Electron Impact

Abstract: Relative abundances and appearance potentials are reported for both positive and negative ions observed in the mass spectrum of perchlorylfluoride. Appearance potentials of the atom ions result in a value for ΔHf(ClO3F) of nearly zero within the experimental uncertainty. Bond dissociation energies and ionization potentials of the chloryl radicals are estimated from appearance potentials of the polyatomic ions. The energetics of probable ionization-dissociation processes are compared with observed data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

1958
1958
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…The best calculated value (Q5) is more positive than the experimental values and just outside of the error bars. For ClO 3 F, three experimental values have been reported for the heat of formation. ,,, Our best computed value for the heat of formation is −2.3 kcal/mol from the Q5 CBS extrapolation, which is too positive as compared to experiment by about 3 kcal/mol and just outside the error bars of the calculation and experiment. Du et al reported the heat of formation of ClO 3 F as 1.5 kcal/mol at the G3 level, slightly more positive than our DTQ extrapolated value of 0.7 kcal/mol.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The best calculated value (Q5) is more positive than the experimental values and just outside of the error bars. For ClO 3 F, three experimental values have been reported for the heat of formation. ,,, Our best computed value for the heat of formation is −2.3 kcal/mol from the Q5 CBS extrapolation, which is too positive as compared to experiment by about 3 kcal/mol and just outside the error bars of the calculation and experiment. Du et al reported the heat of formation of ClO 3 F as 1.5 kcal/mol at the G3 level, slightly more positive than our DTQ extrapolated value of 0.7 kcal/mol.…”
Section: Resultsmentioning
confidence: 70%
“… a Calculations from DTQ CV extrapolated results are given in parentheses for compounds with Br. b Reference . c Reference . d Reference . e Reference . f Reference g Values obtained from reference . h Reference . i Reference . …”
Section: Resultsmentioning
confidence: 99%
“…Indirect estimates of the ionization potentials of Cl02 and ClO have been made from electron impact studies on the ionization and dissociation of perchloryl fluoride. 16 Dibeler et aZ. 16 estimated I(Cl0z) to be 11-1 eV from the appearance potential of ClOi from FClOs.…”
Section: Electron Impact Resultsmentioning
confidence: 99%
“…16 Dibeler et aZ. 16 estimated I(Cl0z) to be 11-1 eV from the appearance potential of ClOi from FClOs. Dibeler's value of A(C1O;) = 15.7+0.5 eV gave an upper limit to AH'j(Cl0;) of 281flOkcalmole-1, the error quoted being in the appearance potential measurement.…”
Section: Electron Impact Resultsmentioning
confidence: 99%
“…Действительно, ток отрицательных ионов, обра-зующихся при энергии электронов, близкой к нулю, более чем в 2 раза превосходит ток наиболее распространенного положительного иона СЮз-При этом ClOgF исключительно стоек термически] и химически инертен 109 . Процессы прилипания электронов с энергией, близкой к нулю, могут идти в очень узкой области энергий.…”
Section: образование отрицательных ионовunclassified